2018
DOI: 10.1177/1524838018801332
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Childhood Abuse on the Commercial Sexual Exploitation of Youth: A Systematic Review and Meta-Analysis

Abstract: Scholars and practitioners have drawn attention to the issue of commercial sexual exploitation (CSE) of minors, yet we continue to lack a clear understanding of which factors increase a minor’s risk to this type of victimization. The current article reviews the literature about the impact of sexual, physical, or emotional abuse on the risk of CSE. The study utilizes quantitative meta-analytical techniques to estimate an overall impact of prior abuse. Nineteen studies were selected after a comprehensive search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 94 publications
3
20
0
1
Order By: Relevance
“…Childhood maltreatment trauma posed the strongest risk factor for CSEC, supported by the majority of studies (e.g., see Chohaney, 2016; Franchino-Olsen, 2019; Havlicek et al, 2016; O’Brien et al, 2017; Reid, 2014; Reid et al, 2015), thus corroborating findings of an earlier systematic review by Choi (2015) and a meta-analysis by De Vries and Goggin (2018). School nurses, as trusted health professionals in the school setting, are uniquely positioned to identify the signs and symptoms of child maltreatment trauma, as child victims of CSA or other forms of abuse are likely to see their school nurse for related physical and psychological health complaints.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Childhood maltreatment trauma posed the strongest risk factor for CSEC, supported by the majority of studies (e.g., see Chohaney, 2016; Franchino-Olsen, 2019; Havlicek et al, 2016; O’Brien et al, 2017; Reid, 2014; Reid et al, 2015), thus corroborating findings of an earlier systematic review by Choi (2015) and a meta-analysis by De Vries and Goggin (2018). School nurses, as trusted health professionals in the school setting, are uniquely positioned to identify the signs and symptoms of child maltreatment trauma, as child victims of CSA or other forms of abuse are likely to see their school nurse for related physical and psychological health complaints.…”
Section: Discussionsupporting
confidence: 81%
“…Building on a systematic review (Choi, 2015) and on a meta-analysis (De Vries & Goggin, 2018), both of which assess only a few CSEC risk factors specifically for girls, the purpose of this review of the literature is to provide a comprehensive overview of the major risk factors for CSEC of girls aged 12–18, the largest group of victims of CSEC in the United States, as well as to critically appraise the quality of the literature.…”
mentioning
confidence: 99%
“…Two recent reviews by Carr, Duff, and Craddock (, ) similarly found that CSA survivors were at a higher risk of a range of psychosocial, physical and mental health difficulties. Systemic reviews have also specifically established that CSA is a risk factor for depression, anxiety, Post Traumatic Stress Disorder (PTSD) (Amado, Arce, & Herraiz, ; Hillberg, Hamilton‐Giachritsis, & Dixon, ); sexual exploitation (De Vries & Goggin, ), intimate partner violence (Li, Zhao, & Yu, ), suicidality (Angelakis, Gillespie & Panagioti, ), substance abuse (Halpern et al, ), and educational difficulties (Fry et al, ). Reviews have also demonstrated a range of psychosocial protective factors that can help reduce risk, including family and social supports, personal attributes, active coping style, a sense of personal influence, and externalising blame for the abuse (Carr, Duff, & Craddock, , ).…”
Section: Introductionmentioning
confidence: 99%
“…While there is no consensus about which risk items matter and to what degree, risk items are expected to be found at multiple ecological levels including individual characteristics, family, and peer influences. Examples that are empirically supported by research are sexual abuse, substance use, and runaway histories or homelessness (De Vries & Goggin, 2018; Edwards, Iritani, & Hallfors, 2006; Martin, Hearst, & Widome, 2010; Reid, 2011; Reid & Piquero, 2014; Roe-Sepowitz, 2012). These items have shown to increase risk of CSEC in a general population of minors, although the items that signal general risk are likely different from the items representing immediate risk of CSEC among a high-risk population.…”
Section: Assessing Risk Of Csecmentioning
confidence: 99%
“…The literature is insufficient for two key reasons. First, prior work has focused on how CSEC victims differ from a general population of youth because of histories of childhood adversities, including sexual abuse, runaway histories, substance abuse, and involvement with child welfare, juvenile justice, and health-care systems (see De Vries & Goggin, 2018; Gibbs, Henninger, Tueller, & Kluckman, 2018; Greenbaum, Dodd, & McCracken, 2018; Kotrla, 2010; Salisbury, Dabney, & Russell, 2015). While these childhood adversities increase vulnerability to CSEC victimizations compared to youths without such experiences, little is known about what signals immediate vulnerability to CSEC among groups of young people who have already been identified as being at higher risk of victimization (see, for recent work in this area, Panlilio, Miyamoto, Font, & Schreier, 2019).…”
mentioning
confidence: 99%